Case Report: Ethanol ablation of the Marshall vein as the first step for left atrial tachycardia ablation - Ozgeyik, Mehmet; Dural, Ibrahim Etem; Baysal, Erkan; Li, Anthony; Candemir, Basar (Frontiers in Cardiovascular Medicine, 2024)
Electroanatomic mapping guides complex atrial tachycardia ablations, however challenges may emerge post-pulmonary vein isolation. 3D mapping systems can show the mechanism of tachycardia and critical areas that need to be ablated. Sometimes, these areas may be deeper than endocardial ablation can successfully reach. In a unique case, vein of Marshall (VOM) ethanol ablation, a conventional secondary intervention, promptly terminated a Marshall-bundle related atrial tachycardia without further endocardial radiofrequency application, suggesting VOM ethanol ablation as a potential primary strategy.